Dry and steam reforming of biomass pyrolysis gas for rich hydrogen gas. (July 2015) - Xu, Xiwei; Jiang, Enchen; Wang, Mingfeng; Xu, Youjie
Abstract: Biomass pyrolysis gas (including H2, CO, CH4, CO2, C2 H4, C2 H6 and etc.) reforming for hydrogen production over Ni/Fe/Ce/Al2 O3 catalysts was presented in this study. This study investigated how the operating conditions, such as the calcinations temperature of catalysts, the reaction temperature, the gas hourly space velocity (GHSV) and the ratio of H2 O/C, affect the conversion of CH4 and CO2 and the selectivity of hydrogen from dry and steam reforming of pyrolysis gas. The experimental results indicated that, under the conditions: the reaction temperature of 600 °C, the GHSV of 900 h −1 and H2 O/C of 0.92, the reaction efficiency is the optimal. Especially, the concentration of H2, CO, CH4, CO2, and C2 Hn (C2 H4 and C2 H6 ) were 36.80%, 10.48%, 9.61%, 42.62%, 0.49% respectively. The conversion of CH4 and CO2 reached 45.9% and 51.09%, respectively. There were all kinds of reactions during the processing of reforming of pyrolysis gas. And the main reactions changed with the operation condition. It was due to the promoting or inhibiting interaction among different constituents in the pyrolysis gas and the different activity of catalysts in the different operation condition. Graphical abstract: The pyrolysis gas, which accounts for about one third of agriculture waste in weight, can be obtained from the pyrolysis of agricultural and forestry waste. It is composed of H2, CO, CH4, CO2, C2 H4, C2 H6, which could be used as the H-donor for hydrodeoxygenation of bio-oil or applies in automotive internal combustion engines after steam catalytic reforming. Biomass pyrolysis gas reforming for hydrogen production over Ni/Fe/Ce/Al2 O3 catalysts was presented in this study. Highlights: Pyrolysis gas (H2, CO, CH4, CO2, C2 H4, C2 H6 ) is the raw material to produce H2 . Ni/Fe/Ce/Al2 O3 catalysts effectively boost the concentration and yield of hydrogen. The dominant reactions varied with process condition. H2 selectivity is optimal with dry reforming and water-gas shift reactions co-exist.